Effect of conservation agriculture on soil fungal diversity in rice-wheat-greengram cropping system in eastern Indo-Gangetic plains of South Asia - Kumar, Rakesh; Choudhary, Jaipal Singh; Naik, Sushanta Kumar; Mishra, Janki Sharan; Banra, Sushmita; Poonia, Shish Pal; Mondal, Surajit; Das, Anup; Rao, Karnena Koteswara; Kumar, Virender; Bhatt, Bhagwati Prasad; Chaudhari, Suresh Kumar; et al. (Frontiers in Microbiology, 2024)
Conservation agriculture (CA) is emerging as an eco-friendly and sustainable approach to food production in South Asia. CA, characterized by reduced tillage, soil surface cover through retaining crop residue or raising cover crops, and crop diversification, enhances crop production and soil fertility. Fungal communities in the soil play a crucial role in nutrient recycling, crop growth, and agro-ecosystem stability, particularly in agricultural crop fields.This study investigates the impact of seven combinations of tillage and crop residue management practices of agricultural production systems, including various tillage and crop residue management practices, on soil fungal diversity. Using the Illumina MiSeq platform, fungal diversity associated with soil was analysed. The results show that the partial CA-based (pCA) production systems had the highest number of unique operational taxonomic units (OTUs) (948 OTUs) while the conventional production system had the lowest number ( 665OTUs). The major fungal phyla identified in the top soil (0-15 cm) were Ascomycota, Basidiomycota, and Mortierellomycota, with their abundance varying across different tillagecum-crop establishment (TCE) management methods. Phylum Ascomycota was the dominant in CA-based management treatments (94.9±0.62), followed by the partial CA (pCA)-based treatments (91.0 ± 0.37). Therefore, CA-based production systems play a crucial role in shaping soil fungal diversity, highlighting their significance for sustainable agricultural production.